Effectiveness of a Pharmacist-Led Structured Group-Based Educational Programme on Improving Medication Adherence and Glycaemic Control of Patients with Type 2 Diabetes Mellitus among Malay Communities in Sarawak, Malaysia - Ting, Chuo Yew (Universiti Malaysia Sarawak (UNIMAS), 2021)
A pharmacist-led structured group-based intervention (MEDIHEALTH) was formulated to improve medication adherence among Malay type 2 diabetes mellitus (T2DM) patients in the Malaysian state of Sarawak. The objective of this study was to examine the effectiveness of MEDIHEALTH and its mechanism of impact for improving medication adherence and the glycated haemoglobin (HbA1c) level. A two group and parallel randomized controlled trial with a twelve months follow-up period was conducted at two primary health clinics in Malaysia that were surrounded by Malay communities. Malay T2DM patients whose HbA1c was > 7% and total score on the Self-Efficacy for Appropriate Medication Use Scale (SEAMS) was < 26 were recruited and parallelly randomized to the MEDIHEALTH or usual care (control) groups. The extended theory of planned behaviour was employed to test the mechanism of impact. Repeated measure analysis of variance was used to assess the difference in the estimated marginal mean of the SEAMS scores and HbA1c level between the intervention and control groups at different times. A total of 142 participants were recruited and randomized; three from the intervention group and eight from the control group withdrew before receiving any intervention. Hence, 68 participants in the intervention group and 63 in the control group were included for analyses. The MEDIHEALTH group had significantly greater increases in the SEAMS scores compared to the control group (p < 0.001) at one (33.97 versus 22.36), three (34.31 versus 22.44), six (35.17 versus 23.23) and twelve (34.94 versus 23.65) months post-intervention. There were also significantly greater reductions in HbA1c levels in the MEDIHEALTH group compared to the control group (p < 0.001) at three (7.87 versus 9.45), six (7.62 versus 9.04) and twelve (7.62 versus 9.08) months post-intervention. These improvements were mediated by enhancements in perceived behavioural control and knowledge about medications. The MEDIHEALTH may improve medication adherence and glycaemic control among Malay T2DM patients.